Clinical evidence and potential mechanisms of traditional Chinese medicine for refractory heart failure: a literature review and perspectives - Guo, Liuli; Yang, Zhihua; Feng, Wenshuai; Liu, Yiman; Li, Zhenzhen; Zhuang, Pengwei; Ren, Ming (Frontiers in Cardiovascular Medicine, 2024)
Refractory heart failure (RHF), or end-stage heart failure, has a poor prognosis and high case fatality rate, making it one of the therapeutic difficulties in the cardiovascular field. Despite the continuous abundance of methods and means for treating RHF in modern medicine, it still cannot meet the clinical needs of patients with RHF. How to further reduce the mortality rate and readmission rate of patients with RHF and improve their quality of life is still a difficult point in current research. In China, traditional Chinese medicine (TCM) has been widely used and has accumulated rich experience in the treatment of RHF due to its unique efficacy and safety advantages. Based on this, we comprehensively summarized and analyzed the clinical evidence and mechanism of action of TCM in the treatment of RHF and proposed urgent scientific issues and future research strategies for the treatment of RHF with TCM, to provide reference for the treatment of RHF.